Pengaruh Pemberian Jus Buah Belimbing Terhadap Perubahan Tekanan Darah Penderita Hipertensi Di Panti Jompo - Vetri Nathalia (Jurnal Pembangunan Nagari, 2017)
Hypertension is a major and serious problem in life, in addition to its prevalence is high and likely to increase in the future, the level of ferocity was also high (Sufrida & Maloedyn 2006). In the treatment of hypertension are many natural herbs that can be taken, one of which carambola fruit. Carambola fruit can regulate kidney diuresis in patients with hypertension. This study aims to determine the effect of Carambola fruit juice to changes in blood pressure in hypertensive patients in nursing homes. The study was conducted from March to July 2016 with Quasi Experimental methods. The study was conducted for 7 days with a sample of 10 people, divided into two groups of control and experiment. The results showed in 5 respondents were given carambola fruit juice changes in blood pressure with an average difference in systolic blood pressure before and after giving the P value = 0.014 means that there is a significant difference between the blood pressure before and after administration of carambola fruit juice. From these results it can be concluded no difference in mean blood pressure before and after the carambola fruit juice to it advised the public, especially the elderly in nursing homes to be able to take advantage of carambola fruit juice in reducing press.